Предмет: Алгебра,
автор: Аноним
Разложить на множители:
а) ав-ас-вх+сх+с-в
в)х^2+2хс+с^2
Ответы
Автор ответа:
1
1)b(a-x-1)-c(a-x-1)=(a-x-1)(b-c)
2)(x+c)²
2)(x+c)²
Автор ответа:
1
а) ab-ac-bx+cx+c-b=
=b(a-x-1)-c(a-x-1)=(b-c)(a-x-1)
b)x^2+2xc+c^2=(a+c)^2
=b(a-x-1)-c(a-x-1)=(b-c)(a-x-1)
b)x^2+2xc+c^2=(a+c)^2
Похожие вопросы
Предмет: История,
автор: Dfu59
Предмет: Математика,
автор: fevraleva2
Предмет: Математика,
автор: styagina83
Предмет: Математика,
автор: Dudeposka
Предмет: Алгебра,
автор: sapden